The aerodynamic characteristics of a family of related hovercraft shapes - Andrews, E. J. (College of Aeronautics, 1967)
The handling qualities of hovercraft indicate the need for a better understanding of the influence of the basic aerodynamic characteristics. This report is the first of a series in which the aerodynamic characteristics of hovercraft shapes are studied with particular reference to current design variables starting with simple solid block models and progressing to more sophisticated hollow models having cushion efflux and air-induction.